PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Dede Rubai Misbahul Alam; Kusnadi Kusnadi (Jurnal Kinerja, 2023)
This This study aims to determine the leadership role of school principals in improving teacher performance. The research was conducted at SDIT Annur Cikarang Center, Bekasi Regency. This study uses a qualitative approach with data collection techniques through interviews, observation and documentation. The subject of this research is the principal of the school. The resource persons were foundations as superiors, deputy principals, and teacher representatives from level 1, level 3 and level 6. The research location was in a private school which is located at Jalan Raya Rabbit block R7 Number 1 Cikarang Pusat, Bekasi Regency. The results of the study show that the role of the school principal is in improving teacher performance through coaching teachers by participating in trainings that are held both internally and externally, the role of the principal is also to supervise through supervision activities to see directly the learning process in class, the role of the principal schools also provide motivation to teachers either verbally or in the form of awards for outstanding teachers, as well as the role of the principal in improving performance through evaluation to measure the level of success and weaknesses of teachers. The conclusions from this study indicate that the principal plays a role in increasing teacher performance. This shows that the principal has carried out his duties and functions properly.